Spatial distribution of chickpea ascochyta blight (Ascochyta rabiei) and analyses of biophysical factors influencing disease epidemics in northwestern Ethiopia - Addisu Mandefro; Getnet Yitayih; Girmay Aragaw (PLoS ONE, 2025)
Chickpea (Cice rarietinum L.) is one of the important grain legume crops in Ethiopia, which serves as a source of both foreign exchange and food. However, the crop production and productivity are currently challenged by ascochyta blight disease caused by Ascochyta rabiei in the study areas.A total of 120 chickpea fields were assessed from five districts in two zonesduring the 2022 main cropping season to assess the distribution, prevalence, and intensity of ascochyta blight of chickpea and its association with agro-ecological factors in northwestern Ethiopia.The results confirmed a 100% prevalence of ascochytablight disease across districts. The highest disease incidence (46.32%) and severity (32.90%) were assessed from Fogera and GondarZuria districts, respectively. The associations between disease parameters and biophysical factors were performed using a binary logistic regression model.High incidence (>40%) and severity (>25%) were strongly associated with mixed cropping, Fogera and Gondar Zuria districts, ≤ two times land preparation, Vertisol soil type, desi chickpea type, and broadleaf weed type in the model. Lower disease incidence (≤ 40%) and severity (≤ 25%) had a strong association with sole cropping, more than two times land preparation, Nitisolsoil type, and growing of kabuli chickpea type. Thus, planting chickpea in sole cropping, more than two times land preparation, growing chickpea in Nitisol soil and use of kabuli chickpea typecould be used as management options to reduce the impact of the disease in northwestern Ethiopia and other similar ecological areas of the country.